Pengaruh Volume Pembiayaan Dan Restrukturisasi Pembiayaan Terhadap Profitabilitas Bank Syariah Di Indonesia - Agustuty, Lasty; Alam, Andi Rifqah Purnama; Hariyanti, Hariyanti (STIM-LPI Makassar, 2025)
This study aims to examine the effect of financing volume and financing restructuring on the profitability of Islamic banks in Indonesia. The sample used in this study was 5 Islamic banks in Indonesia that presented complete quarterly financial reports for the period 2021-2023. The analysis method used is multiple linear regression of panel data. The results of the study indicate that financing volume has a positive and significant effect on the profitability (ROA) of Islamic banks, while financing restructuring has a negative and significant effect on the profitability (ROA) of Islamic banks in Indonesian